Endothelial Retargeting of AAV9 In Vivo. Issue 7 (12th January 2022) - Bozoglu, Tarik; Lee, Seungmin; Ziegler, Tilman; Jurisch, Victoria; Maas, Sanne; Baehr, Andrea; Hinkel, Rabea; Hoenig, Amelie; Hariharan, Anjana; Kim, Christina Inyeop; Decker, Simon; Sami, Haider; et al.
Abstract: Adeno‐associated viruses (AAVs) are frequently used for gene transfer and gene editing in vivo, except for endothelial cells, which are remarkably resistant to unmodified AAV‐transduction. AAVs are retargeted here toward endothelial cells by coating with second‐generation polyamidoamine dendrimers (G2) linked to endothelial‐affine peptides (CNN). G2 CNN AAV9‐Cre (encoding Cre recombinase) are injected into mTmG‐mice or mTmG‐pigs, cell‐specifically converting red to green fluorescence upon Cre‐activity. Three endothelial‐specific functions are assessed: in vivo quantification of adherent leukocytes after systemic injection of ‐ G2 CNN AAV9 encoding 1) an artificial adhesion molecule (S1FG) in wildtype mice (day 10) or 2) anti‐inflammatory Annexin A1 (Anxa1) in ApoE −/− mice (day 28). Moreover, 3) in Cas9‐transgenic mice, blood pressure is monitored till day 56 after systemic application of G2 CNN AAV9‐gRNAs, targeting exons 6–10 of endothelial nitric oxide synthase (eNOS), a vasodilatory enzyme. G2 CNN AAV9‐Cre transduces microvascular endothelial cells in mTmG‐mice or mTmG‐pigs. Functionally, G2 CNN AAV9‐S1FG mediates S1FG‐leukocyte adhesion, whereas G2 CNN AAV9‐Anxa1‐application reduces long‐term leukocyte recruitment. Moreover, blood pressure increases in Cas9‐expressing mice subjected to G2 CNN AAV9‐gRNA eNOS . Therefore, G2 CNN AAV9 may enable gene transfer in vascular and atherosclerosis models. Abstract : A combination of polyamidoamine nanoparticle of second generation (G2) coating and endothelial‐affine peptide targeting is applied to alter the tropism of AAV9 from myo‐ and liver‐tropism to endothelial cells. Successful retargeting of G2 CNN ‐coated AAV9 via fluorescence microscopy and three functional assays depending on endothelial transduction of the transgene is demonstrated. This retargeting renders AAV9 utilizable for vascular investigations.